Flexibility of short ds-DNA intercalated by a dipyridophenazine ligand - Jia, Fuchao; Despax, Stéphane; Münch, Jean-Pierre; Hébraud, Pascal (Frontiers in Chemistry, 2015)
We use Förster Resonant Energy Transfer (FRET) in order to measure the increase of flexibility of short ds-DNA induced by the intercalation of dipyridophenazine (dppz) ligand in between DNA base pairs. By using a DNA double strand fluorescently labeled at its extremities, it is shown that the end-to-end length increase of DNA due to the intercalation of one dppz ligand is smaller than the DNA base pair interdistance. This may be explained either by a local bending of the DNA or by an increase of its flexibility. The persistence length of the formed DNA/ligand is evaluated. The described structure may have implications in the photophysical damages induced by the complexation of DNA by organometallic molecules.